Exploring the economic dimensions of human resource management: a systematic literature review - Shah, Syed Qasim; Mhd. Sarif, Suhaimi (Global Illuminators, 2023)
In this comprehensive systematic literature review, we delve into the intricate synergy between Human Resource Management(HRM) and economics, unraveling the profound impact of economic principles on HRM strategies and practices. Examining recent scholarly works, we illuminate how economic theories shape HR decision-making, providing fresh insights into the complex relationship between human capital and financial outcomes. We uncover how economic factors influence compensation structures, turnover dynamics, and resource allocation strategies, underlining their tangible effects on organizational success. However, we also underscore the nuanced challenges of aligning HRM with economic objectives, particularly amidst technological advancements, gig economy shifts, and sustainability concerns. As we conclude, we advocate for further research, urging exploration into AI-infused HR economics, the evolving workforce landscape, and the interconnectedness of HR practices and societal well-being. Through a multidisciplinary lens, our study advances comprehension of the economic foundations of HRM, guiding organizations towards holistic strategies that unite human capital with financial achievement.